Optimization of plectranthus amboinicus (Lour.) spreng extraction process using microwave-assisted technique - Samad, N.A.; Zaidel, D.N.A.; Salleh, E.; Yusof, A.H.M; Dailin, D.J (Italian Association of Chemical Engineering - AIDIC, 2019)
Plectranthus amboinicus (Lour.) Spreng is a medicinal herb with bioactive compounds and known to have pharmacological properties. To obtain the extract of this herb, efficient extraction technique with high extraction rates is needed. Microwave-assisted extraction (MAE) is a green extraction technique with shorter irradiation time, less solvent used and lower CO2 emission compared to other conventional extraction methods. The objective of the study was to determine the optimum operating extraction condition of P. amboinicus using MAE by varying the irradiation time, solvent concentration and solvent-to-solid ratio to obtain optimum yield extract and conducted using response surface methodology (RSM). The extract obtained at optimum condition was characterized for its antioxidant properties. The RSM results show that the optimum condition of P. amboinicus extraction was at 2 min, 30 % ethanol concentration and solvent-to-solid ratio at 30 mL/g with yield extract obtained at 39.81 wt %. The result antioxidants activity of the P. amboinicus extract showed IC50 value of 4.63 mg/mL while the inhibition of DPPH radical scavenging activity from the trolox standard was 5.48 ± 0.77 mg trolox equivalents (TEQ)/g extract. The study proved MAE is a better alternative compared to conventional extraction method with 16.8 % higher yield and the extract of P. amboinicus can be potentially applied in healthcare and pharmaceutical industry.